Modeling Technology Adoption in Developing Countries - Besley, Timothy; Case., A Betty (American Economic Review, 1993)
An analysis of technology adoption decisions by poor farmers is provided. Some possible empirical models for studying technology adoption are reviewed. The issue of theoretical consistency is dealt with in terms of the costs of such consistency, measured in data needs and model complexity, and the benefits, measured in terms of understanding the micro-economic foundations of adoption.